2012
DOI: 10.1007/s10722-012-9877-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of five novel low molecular weight glutenin subunit genes from Tibetan wheat landraces (Triticum aestivum L.)

Abstract: The low molecular weight glutenin subunits (LMW-GS) are the major components of glutenins and are important for the end-use quality of wheat. Five novel LMW-GS genes (designated as LMW-Jiachazharen, LMW-Bangdadongmai-3, LMWJiachaaigan, LMW-Maoyintumai and LMW-Rikezehongmai) were isolated from Tibetan wheat landraces. The coding regions of LMW-Jiachazharen, LMWBangdadongmai-3, LMW-Jiachaaigan, LMW-Maoyintumai and LMW-Rikezehongmai were 912, 897, 915, 927 and 906 bp in length, which encoded 302, 297, 303, 307 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 20 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…The same number of cysteine residues was present in the LMW-m gene AY263369, which was probably associated with good properties of Chinese wheat cultivar Xiaoyan 6 (Zhao et al 2004). It has been suggested that the additional cysteine residue in LMW subunits might lead to a higher cross linkage with other glutenin subunits, which contributes to enhanced dough properties (Lan et al 2013). Comosa-M1 possessed seven cysteine residues, with the first cysteine residue replaced by tyrosine.…”
Section: Discussionmentioning
confidence: 99%
“…The same number of cysteine residues was present in the LMW-m gene AY263369, which was probably associated with good properties of Chinese wheat cultivar Xiaoyan 6 (Zhao et al 2004). It has been suggested that the additional cysteine residue in LMW subunits might lead to a higher cross linkage with other glutenin subunits, which contributes to enhanced dough properties (Lan et al 2013). Comosa-M1 possessed seven cysteine residues, with the first cysteine residue replaced by tyrosine.…”
Section: Discussionmentioning
confidence: 99%
“…Ribeiro et al (2013) analyzed the Portuguese wheat landrace 'Barbela' and reported a new x-type HMW-GS encoded at the Glu-A1 locus that was named 1Ax1.1. Lan et al (2013) reported low-molecular weight glutenin subunits as the major components of glutenins, which were considered to be important for the end-use quality of wheat; however, Kaur et al (2013) reported the physico-chemical and rheological properties of Indian wheat cultivars varying in HMW-GS. Pompa et al (2013) reported that the gluten composition and expression influenced dough properties and were cultivar-and environment-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…However, in different papers, this terminology has already been applied ([22,23] just to cite the most recent ones).…”
Section: Discussionmentioning
confidence: 99%